2021
DOI: 10.1002/advs.202102381
|View full text |Cite
|
Sign up to set email alerts
|

Small Extracellular Vesicles Propagate the Inflammatory Response After Trauma

Abstract: Trauma is the leading cause of death in individuals under 44 years of age. Thorax trauma (TxT) is strongly associated with trauma‐related death, an unbalanced innate immune response, sepsis, acute respiratory distress syndrome, and multiple organ dysfunction. It is shown that different in vivo traumata, such as TxT or an in vitro polytrauma cytokine cocktail trigger secretion of small extracellular nanovesicles (sEVs) from endothelial cells with pro‐inflammatory cargo. These sEVs transfer transcripts for ICAM‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 114 publications
1
31
1
Order By: Relevance
“…Since it has been shown that EVs are involved in multisystemic signaling mediating regeneration and long-term adaptive responses [ 40 , 41 ], based on our findings as well, it is reasonable to assume that SIRT of the liver could have systemic implications on the immune system. In a recent study, a decrease in CD4 and CD8 carrying EVs was demonstrated, while the number of CD69 carrying EVs in the circulation of CCA patients was increased compared to HVs.…”
Section: Discussionsupporting
confidence: 57%
“…Since it has been shown that EVs are involved in multisystemic signaling mediating regeneration and long-term adaptive responses [ 40 , 41 ], based on our findings as well, it is reasonable to assume that SIRT of the liver could have systemic implications on the immune system. In a recent study, a decrease in CD4 and CD8 carrying EVs was demonstrated, while the number of CD69 carrying EVs in the circulation of CCA patients was increased compared to HVs.…”
Section: Discussionsupporting
confidence: 57%
“…TxT experiments were conducted by inducing a defined bilateral lung contusion using an air pressure blast wave on anesthetized 12-week old male C57BL/6 animals (14). The level of pulmonary contusion was chosen based on histologic, cardiopulmonary as well as immunologic changes in earlier studies and was sufficient to induce a profound local and systemic inflammatory response, but without being lethal itself (16).…”
Section: Thorax Trauma Polytrauma As Well As Polytrauma With Hemorrha...mentioning
confidence: 99%
“…Moreover, Seibold et al suggested that extracellular vesicles secreted on thorax trauma are strongly associated with sepsis and biochemical markers of AKI (110). The authors further showed the thorax trauma–responding extracellular vesicles might originate from endothelial cells and contain endothelial activators, such as vascular cell adhesion molecule 1, E‐selectin, and cytokines (110). In contrast, there is some evidence for therapeutic roles of extracellular vesicles during sepsis-associated AKI.…”
Section: Inflammationmentioning
confidence: 99%